Global foot-and-mouth disease risk assessment based on multiple spatial analysis and ecological niche model - Qi An; Yiyang Lv; Yuepeng Li; Zhuo Sun; Xiang Gao; Hongbin Wang (Veterinary Quarterly)
Foot-and-Mouth Disease is a highly contagious transboundary animal disease. FMD has caused a significant economic impact globally due to direct losses and trade restrictions on animals and animal products. This study utilized multi-distance spatial cluster analysis, kernel density analysis, directional distribution analysis to investigate the spatial distribution patterns of historical FMD epidemics. A multi-algorithm ensemble model considering climatic, geographic, and social factors was developed to predict the suitability area for FMDV, and then risk maps of FMD for each species of livestock were generated in combination with the distribution of livestock. The results show that all serotypes of FMD exhibit significant clustering with a clear tendency toward a directional distribution. Serotypes A and O are widespread in Asia, Europe, Africa, and South America. Serotype Asia 1 is prevalent in Asia. Serotype SAT2 is prevalent in Africa and the Middle East, while Serotypes SAT1 and SAT3 are restricted to Africa. Ecological niche modeling reveals temperature, precipitation, wind speed, and vegetation are important factors influencing the occurrence of FMD. Except for buffaloes, the distribution of high-risk areas for FMD occurrence in other livestock species is quite widespread. The areas primarily include the southern region of North America, the northern, southern, and eastern regions of South America, the Mediterranean region, the eastern region of Europe, the central and southern regions of Africa, the central, eastern, and southern regions of Asia, and parts of Australia. These findings will provide valuable insights into the prevention and control of FMD.